Restrictive cardiomyopathy: from genetics and clinical overview to animal modeling - Michelle Chintanaphol; Buyan-Ochir Orgil; Neely R. Alberson; Jeffrey A. Towbin; Enkhsaikhan Purevjav (Reviews in Cardiovascular Medicine, 2022)
Restrictive cardiomyopathy (RCM), a potentially devastating heart muscle disorder, is characterized by diastolic dysfunction due to abnormal muscle relaxation and myocardial stiffness resulting in restrictive filling of the ventricles. Diastolic dysfunction is often accompanied by left atrial or bi-atrial enlargement and normal ventricular size and systolic function. RCM is the rarest form of cardiomyopathy, accounting for 2–5% of pediatric cardiomyopathy cases, however, survival rates have been reported to be 82%, 80%, and 68% at 1-, 2-, and 5-years after diagnosis, respectively. RCM can be idiopathic, familial, or secondary to a systemic disorder, such as amyloidosis, sarcoidosis, and hereditary hemochromatosis. Approximately 30% of cases are familial RCM, and the genes that have been linked to RCM are cTnT, cTnI, MyBP-C, MYH7, MYL2, MYL3, DES, MYPN, TTN, BAG3, DCBLD2, LNMA, and FLNC. Increased Ca2+ sensitivity, sarcomere disruption, and protein aggregates are some of the few mechanisms of pathogenesis that have been revealed by studies utilizing cell lines and animal models. Additional exploration into the pathogenesis of RCM is necessary to create novel therapeutic strategies to reverse restrictive cardiomyopathic phenotypes.